2022
DOI: 10.1542/peds.2022-056567
|View full text |Cite
|
Sign up to set email alerts
|

Sex Assigned at Birth Ratio Among Transgender and Gender Diverse Adolescents in the United States

Abstract: OBJECTIVE: Representatives of some pediatric gender clinics have reported an increase in transgender and gender diverse (TGD) adolescents presenting for care who were assigned female sex at birth (AFAB) relative to those assigned male sex at birth (AMAB). These data have been used to suggest that youth come to identify as TGD because of “social contagion,” with the underlying assumption that AFAB youth are uniquely vulnerable to this hypothesized phenomenon. Reported changes in the AMAB:AFAB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 22 publications
1
31
1
Order By: Relevance
“…In terms of the generalizability of our study findings, it is important to note that our study sample represented a gender clinic–referred cohort of TGD young people that represents only a small proportion of the entire TGD youth population; this is an important consideration given differences in nonclinical vs clinical samples. 49 , 50 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the generalizability of our study findings, it is important to note that our study sample represented a gender clinic–referred cohort of TGD young people that represents only a small proportion of the entire TGD youth population; this is an important consideration given differences in nonclinical vs clinical samples. 49 , 50 …”
Section: Discussionmentioning
confidence: 99%
“…Given that the Trans20 study is now following up these same young people longitudinally, it will therefore be critical to continue to assess QOL over subsequent data waves; this should enable us to move beyond identifying associations and instead make causal inferences. In terms of the generalizability of our study findings, it is important to note that our study sample represented a gender clinic–referred cohort of TGD young people that represents only a small proportion of the entire TGD youth population; this is an important consideration given differences in nonclinical vs clinical samples …”
Section: Discussionmentioning
confidence: 99%
“…The sample consisted of a predominantly adolescent (pubertal) group and the majority were assigned female at birth, which limits study generalisability and comparison. However, the demographics of the sample does re ect the higher proportion of pubertal assigned female at birth young people referred to gender services, both in the GIDS [6, 19,32], and elsewhere [7,8,41], although more recent assessment of community samples indicate a more even ratio in the United States [42].…”
Section: Limitationsmentioning
confidence: 99%
“…GD has traditionally been introduced as a rare condition predominant in assigned males at birth (AMABs) 2. However, recent studies have shown an upward trend in assigned females at birth (AFABs) with a dramatic reversal of the AMAB:AFAB ratio 3–5. The actual AMAB:AFAB ratio varies by age group and study population 4–6.…”
Section: Introductionmentioning
confidence: 99%